Changes in the essential oil content and composition of Salvia limbata C.A. Mey at different growth stages and altitudes. (29th April 2021) - Saffariha, Maryam; Azarnivand, Hossein; Zare Chahouki, Mohammad Ali; Tavili, Ali; Nejad Ebrahimi, Samad; Jahani, Reza; Potter, Daniel
Abstract: Salvia limbata is of great importance to the pharmaceutical industry owing to its various biological effects. Therefore, it is important to investigate the main factors that affect its essential oil composition. Although some investigations have been performed with regard to the phytochemistry of S. limbata, this study investigates, for the first time, the effect of growth stage and altitude on the content and chemical composition of essential oil extracted from S. limbata . For this purpose, the essential oil was extracted from 45 air‐dried samples by hydrodistillation and analyzed by GC–MS and GC–flame methods. The highest content of essential oil was obtained from aerial parts in the vegetative stage at an altitude of 1500 m (0.86% v/w). Our findings show that the vegetative stage at 1500 m is the optimal harvest time to extract the highest content of oil while the highest content of monoterpenes (including α‐pinene and β‐pinene) could be obtained in the same phenological stage at 2000 m. By contrast, the content of sesquiterpenes increased to the highest values in the ripening stage at 1500 and 2500 m. The results of this study help to find the optimal conditions to obtain the highest content of S. limbata essential oil, but additional studies are warranted.